2007
DOI: 10.1007/s10663-007-9052-1
|View full text |Cite
|
Sign up to set email alerts
|

Does a “survival-by-exporting” effect for SMEs exist?

Abstract: The trade literature has long discussed the existence of some benefits attributed to exporting (learning-by-exporting), among others, the improvement in survival chances. This paper examines whether exporting SMEs enjoy better survival prospects than non-exporting SMEs. We investigate the determinants of survival of exporting and non-exporting SMEs and explore whether the exporting behaviour plays a significant role in explaining their probability of exit. For this purpose, we estimate discrete time proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…A high level of innovative activity in an industry may make entry more risky; consequently, the effect on new firm survival should be negative (Audretsch 1991). The chance of survival may, however, depend on a firm's ability to develop specific capabilities, which can be improved by investing in R&D (Esteve-Perez et al 2008). Due to these contradicting effects and empirical results, business survival in science based Pavitt clusters (pavitt_1, pavitt_2, pavitt_3) and in high tech classes (tech1_2) (OCSE taxonomy), where there are more R&D-intensive industries, is also a priori unclear.…”
Section: The Variables and The Expected Signmentioning
confidence: 99%
“…A high level of innovative activity in an industry may make entry more risky; consequently, the effect on new firm survival should be negative (Audretsch 1991). The chance of survival may, however, depend on a firm's ability to develop specific capabilities, which can be improved by investing in R&D (Esteve-Perez et al 2008). Due to these contradicting effects and empirical results, business survival in science based Pavitt clusters (pavitt_1, pavitt_2, pavitt_3) and in high tech classes (tech1_2) (OCSE taxonomy), where there are more R&D-intensive industries, is also a priori unclear.…”
Section: The Variables and The Expected Signmentioning
confidence: 99%
“…However, until the work of Besedeš and Prusa (2006a), less attention has been paid to the study of the risk of exit of exporters. In addition, Esteve-Pérez et al (2008) showed that firms involved in exporting activities face significantly lower probability of failure than non-exporters. Firms enter and exit foreign markets as well as domestic markets.…”
Section: Introductionmentioning
confidence: 99%
“…Brenton et al (2009) also suggested that low exporter survival rates undermined the expansion of export flows from developing countries. In addition, Esteve-Pérez et al (2008) showed that firms involved in exporting activities face significantly lower probability of failure than non-exporters. It is important, therefore, to understand not only the determinants of export entry but also the factors that make new exports sustainable.…”
Section: Introductionmentioning
confidence: 99%
“…While import competition, especially from low-wage countries is generally seen as a driver of plant exit, a new series of studies complicate the links between globalization and firm survival. Thus, plants that export are typically found to be less susceptible to exit than those that do not export (Esteve-Perez et al 2008;Greenaway et al 2008;Gorg and Spaliara 2010). In a different twist, Lopez (2006) shows that plants that import intermediate inputs have a higher probability of survival.…”
Section: Literature Overviewmentioning
confidence: 99%